Development of Audio-Visual Media on the Physical Motor Development of Students in Big Kindergarten - Epi Supriyani Siregar; Imanuddin; Ika Purnama Sari (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2023)
This study aims to determine the effect of the development of audio-visual media on the motor-physical development of students in BIG Kindergarten. This study involved early childhood students aged 5-6 years as participants. An audio-visual-based online learning approach was used in this study to introduce students to interesting physical activities and support the development of their motor skills. This research method use appropriate methods. The proposed solution is the use of audio-visual media which contains games as access to learning materials to develop children's gross motor skills. LCD/Projector is used to display learning videos. The results showed that the audio-visual media developed, including jumping over shapes, hot ball cold ball, cloth rolling ball, light ball, stepping on a tiger's tail, kangaroo ball game, and motion exercises and songs, had a positive influence on students' physical-motor development. Assessments from physical education experts, sports experts, and teachers show that this media gets a high score in the very good category. Based on the results of this study, it can be concluded that the development of audio-visual media in learning gross motor skills has a positive impact on the physical-motor development of early-age students. This media also received a positive response from students and educators, indicating a higher level of motivation and involvement in sports learning. This research contributes to the development of an innovative and effective learning approach in improving gross motor skills of early childhood students.